The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cancers14174271
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic and Stemness Signatures of the High-Risk HCMV Strains in Breast Cancer Progression

Abstract: Background: Human cytomegalovirus (HCMV) oncomodulation, molecular mechanisms, and ability to support polyploid giant cancer cells (PGCCs) generation might underscore its contribution to oncogenesis, especially breast cancers. The heterogeneity of strains can be linked to distinct properties influencing the virus-transforming potential, cancer types induced, and patient’s clinical outcomes. Methods: We evaluated the transforming potential in vitro and assessed the acquired cellular phenotype, genetic and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…In this study, we found that higher HCMV protein expression in breast cancer biopsies at the time of primary diagnosis is significantly associated with a shorter overall survival in patients with breast cancer. Our data provides an important clinical validation to the numerous in vitro and in vivo studies demonstrating that HCMV could play a role in breast cancer pathogenesis [ 11 , 54 , 55 , 56 , 57 , 58 , 71 , 72 ]. These observations were derived from histological analyses performed on a cohort of tissue stained with an automated technique that could be easily applied by others for routine clinical use [ 49 ].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In this study, we found that higher HCMV protein expression in breast cancer biopsies at the time of primary diagnosis is significantly associated with a shorter overall survival in patients with breast cancer. Our data provides an important clinical validation to the numerous in vitro and in vivo studies demonstrating that HCMV could play a role in breast cancer pathogenesis [ 11 , 54 , 55 , 56 , 57 , 58 , 71 , 72 ]. These observations were derived from histological analyses performed on a cohort of tissue stained with an automated technique that could be easily applied by others for routine clinical use [ 49 ].…”
Section: Discussionmentioning
confidence: 55%
“…The role of HCMV as a tumor promoting virus may depend on the viral strain carried by individual patients. Of high concern, certain clinical strains isolated from patients with breast cancer are able to induce oncogenic and stemness signatures in vitro [ 55 , 56 , 57 ]. In our study, HCMV positivity did not correlate statistically with other factors such as subtypes, grading, sex or age.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids likely serve as energy stores that help PGCCs endure stress. 157 The increased lipid droplets may serve as energy storage reservoirs that enable cancer TA B L E 2 Main similarities and differences between dormant PGCCs and cancer cells.…”
Section: 3mentioning
confidence: 99%
“…Characteristics of stem cells, such as self-renewal and differentiation ability 18,157 Expression of the embryonic stem cell markers OCT4, NANOG, SOX2 and SSEA1 138 Can differentiate into adipose, cartilage and bone 18…”
Section: Stemness and Differentiationmentioning
confidence: 99%
“…HCMV-DB and BL, isolated high-risk clinical strains, displayed oncogenic potential in human mammary epithelial cells (HMECs) and replicated in epithelial cells with the interchange of lytic and latent viral cycles promoting the appearance of CMV-transformed HMECs (CTH cells) [60][61][62]. Two additional high-risk HCMV strains, namely biopsy 544 (B544) and B693, recently isolated from enhancer of zeste homolog 2 (EZH2) High Myc High triple-negative breast cancer (TNBC) biopsies revealed oncogenic and stemness potential [63,64]. EZH2 was identified as a downstream target for HCMV-induced Myc upregulation upon HMECs infection with high-risk HCMV strains [64].…”
Section: Oncomodulatory and Oncogenic Properties Of Hcmvmentioning
confidence: 99%